Elisabeth Vigée Le Brun : the odyssey of an artist in an age of revolution - May, Gita (Yale University Press, 2005)
The foremost woman artist of her age, Elisabeth Vigée Le Brun (1755-1842) exerted her considerable charm to become the friend, and then official portraitist, of Marie Antoinette. Though profitable, this role made her a public and controversial figure, and in 1789 it precipitated her exile. In a Europe torn by strife and revolution, this singularly gifted and high-spirited woman nevertheless managed to thrive as an independent, self-supporting artist, doggedly setting up studios in Rome, Naples, Venice, Milan, Vienna, St. Petersburg, and London. Long overlooked or dismissed, Vigée Le Brun's portraits now hang in the Louvre, in a room of their own, as well as in all leading art museums of the world. Illustrations include sixteen of her portraits presented in full color.--From publisher description.